THE DESIGN OF ACQUISITION PARAMETERS ON COMPLEX STRUCTURES USING SPREAD LAYOUT SIMULATION - AYU MAWARDHANI , DITTA
Seismic data acquisition has an important role on seismic exploration activities. In principle, the goal of seismic data acquisition is to get a good seismic data. In turn, a good data quality will result in an accurate seismic data interpretation, which can figure out subsurface geological structures in a hydrocarbon prospect area. In the design of reflection seismic data acquisition, the determination and the choice of geometrical parameters will strongly determine the quality of seismic data which will be gotten. The geometrical parameters to be used among others are : near offset, far offset, interval receiver, interval source, the number of source, fold, and path length. This final project is aimed to search for optimum acquisition parameters which in line with the predicted subsurface model with a case study of complex structure in a steep slope. To get amplitude responses in a required area, spread layout simulation is being done with the separation of area according to its fold coverage in line with acquisition parameter at each shooting. The migration is being done after getting spread layout which considered to be optimum and later on it will be compared with the initial geological structure model. The migration which are being done are Post Stack Time Migration and Pre-Stack Time Migration.